Treatment of holistic suffering in cancer: A systematic literature review. (December 2015) - Best, Megan; Aldridge, Lynley; Butow, Phyllis; Olver, Ian; Price, Melanie A; Webster, Fleur
Background: Holistic suffering is a debilitating problem for cancer patients. Although many treatments have been suggested for its alleviation, they have not been compared for effectiveness. Aim: This literature review seeks to identify what interventions are effective in treatment of holistic suffering of cancer patients. Design: A systematic review was conducted to identify and evaluate studies of interventions for holistic suffering in adult cancer patients. Search terms were generated iteratively from the literature. Data sources: MEDLINE, EMBASE, the Cochrane Library and PsycINFO databases were searched for the years 1992–2015. Included studies were peer-reviewed, English language reports of either a controlled trial or a randomised controlled trial focusing on therapies aimed at relieving suffering in adult cancer patients. Articles were excluded if focused predominantly on spiritual or existential issues or concerns not leading to suffering. Studies were graded for quality using the QualSyst quantitative checklist. Levels of evidence were ascertained by completing the National Health and Medical Research Council criteria. Results are reported according to AMSTAR guidelines. Results: The studies represented seven intervention types. Meaning-centred, hope-centred and stress-reduction interventions were found to be effective. Results of both psycho-educational and spiritual interventions in improving spiritual well-being were mixed. Supportive-expressive interventions – with the exception of forgiveness therapy – were not efficacious. There was little or no evidence for the efficacy of creative and healing arts and other assessed interventions such as animal therapy and haptotherapy. Conclusion: This systematic review found that spiritual well-being, meaning, hope and benefit finding can be positively impacted by a variety of treatment modalities.